2015
DOI: 10.1109/tifs.2015.2404134
|View full text |Cite
|
Sign up to set email alerts
|

The CEO Problem With Secrecy Constraints

Abstract: We study a lossy source coding problem with secrecy constraints in which a remote information source should be transmitted to a single destination via multiple agents in the presence of a passive eavesdropper. The agents observe noisy versions of the source and independently encode and transmit their observations to the destination via noiseless rate-limited links. The destination should estimate the remote source based on the information received from the agents within a certain mean distortion threshold. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…In [71], the Chief Executive Officer (CEO) problem is investigated in which a center controller (or CEO) attempts to minimize the estimate distortion from the noisy observations of a random source it receives. The authors related the equivocation rate 2 to the normalized distortion at the eavesdropper in the CEO problem with additional secrecy constraints, where they showed that the estimation error at the eavesdropper is an upper bound of the equivocation rate.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…In [71], the Chief Executive Officer (CEO) problem is investigated in which a center controller (or CEO) attempts to minimize the estimate distortion from the noisy observations of a random source it receives. The authors related the equivocation rate 2 to the normalized distortion at the eavesdropper in the CEO problem with additional secrecy constraints, where they showed that the estimation error at the eavesdropper is an upper bound of the equivocation rate.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[30]. Motivated by this idea, plus a close relation between MMSE and the mutual information of the channel input and output [32,71], we consider a notion of secrecy in estimation from a non-information theoretic viewpoint by requiring the distortion at the eavesdropper to be greater than a threshold D e . In this way, some level of confidentiality can be achieved at the FC.…”
Section: Multiple Antennas Scenariomentioning
confidence: 99%
See 2 more Smart Citations
“…From an information theoretic perspective, the authors in [19], [20], [21] studied the secrecy capacity in the case of full CSI or partial CSI, and investigated MIMO channels in [22], [23], [24]. Multiterminal source coding or CEO problems with secrecy constraints were also considered in [25], [26], [27], [28]. In particular, in [28], the authors investigated secure lossy source coding in the presence of an eavesdropper who is able to observe the coded information bits and has access to correlated side information.…”
Section: Introductionmentioning
confidence: 99%